Catheter ablation for atrial fibrillation is associated with lower incidence of heart failure and death. Issue 1 (8th October 2019) - Modin, Daniel; Claggett, Brian; Gislason, Gunnar; Hansen, Morten Lock; Worck, Rene; Johannessen, Arne; Hansen, Jim; Svendsen, Jesper Hastrup; Pallisgaard, Jannik L; Schou, Morten; Køber, Lars; Solomon, Scott D; et al.
Abstract: Aims: Catheter ablation for atrial fibrillation (CAF) improves symptoms, but whether CAF improves outcome is less clear. The purpose of this study was to investigate whether CAF is associated with improved outcome in atrial fibrillation (AF) patients with previous direct current (DC) cardioversion. Methods and results: We performed a nationwide cohort study including all patients who underwent their 1st direct current cardioversion for AF in the period 2003–15 ( N  = 25 439). End points were all-cause death, cardiovascular death, stroke/thromboembolism, and incident heart failure (HF). Catheter ablation for AF was treated as a time-varying covariate and the association with outcome was assessed using Cox regression. We also constructed a propensity-matched cohort and assessed the association between CAF and outcome. Median follow-up was 5.3 years (inter-quartile range 3.0–8.7 years). A total of 3509 patients (13.8%) underwent CAF during the study period. Following adjustment for age, gender, comorbidities, medications, educational level, household income, and CHA2DS2VASc score, CAF was associated with reduced risks of all-cause death, cardiovascular death, and incident HF [all-cause death: hazard ratio (HR) 0.69, P  < 0.001; cardiovascular death: HR 0.68, P  = 0.003; incident HF: HR 0.76, P  = 0.011]. Catheter ablation for AF was not associated with a reduced risk of stroke/thromboembolism. These results were replicated in a propensity-matched cohort. Conclusion: In AF patients with a prior DC cardioversion, CAF was associated with a reduced risk of all-cause and cardiovascular death. This may be due to a reduced risk of HF.